Environmentally Friendly Human Resources Management for Indonesia Gold 2045 Container Ports With Maximize Green HRD Port - Amrullah, Romanda Annas; Moejiono, Moejiono; Imanto, Frenki; Arleiny, Arleiny; Rahkman, Rizqi Aini; Prayitno, Prayitno (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
Container ports are one of the investment attractions, the busier the port, the more investment there will be and vice versa, but the success of a port is determined by good service. Environmentally friendly human resources of container ports determine performance improvement. This study uses a qualitative approach method, environmentally based human resources. the data collected is interpreted to produce a deeper understanding of the phenomena observed in the field. The data will then be constructed into themes that have significant meaning. The results of the study found a new concept of Maximize Green Hrd Port which was tested on the management of a container port in Indonesia.